Flooding avoidance Triplaris gardneriana Wedd. (Polygonaceae): growth and morpho-anatomical aspects - Pontara, Vanessa; Bueno, Marcelo Leandro; Scremin-Dias, Edna (Acta scientiarum. Biological sciences, 2016)
The aim of this study was to analyze the effect of flooding in Triplaris gardneriana Wedd, cultivated in drained soil (control) and in flooded condition. The experiment was developed in a greenhouse, using plants with 90 days after the emergency. The response to treatment was evaluated at 0, 30, 60 and 90 days. Growth measurements were made, such as biomass allocation, relative growth rate (RGR). Adventitious roots were not measured only observed, as well as the development of hypertrophied lenticels. The RGR was continuously reduced along the 90 days in flooding conditions for the roots, stem and leaves, compared to control. The flooding of the substrate caused alterations such as: increasing of the cortex width and diameter of the central cylinder of root and increasing the diameter of the vessel element of the root and stem. Results show that T. gardneriana remains under stress when submitted to flooding. Therefore, the production of structures as lenticels, aerenchyma and adventitious roots, structures related to the avoidance of this type of stress, were key factors for the maintenance and survival of T. gardneriana.